ChemInform Abstract: Ring‐Opening Reactions of Oxetanes: A Review of Methodology Development and Synthetic Applications. Issue 45 (October 2016) - Ahmad, Sajjad; Yousaf, Muhammad; Mansha, Asim; Rasool, Nasir; Zahoor, Ameer Fawad; Hafeez, Freeha; Rizvi, Sayyad Muhammad Ali
Abstract: Review: 53 refs.